Clifford Kennedy Berryman papers - Berryman, Clifford Kennedy, 1869-1949.
Correspondence, speech, invitations, printed matter, drawings, and photographs relating primarily to Berryman's career as a political cartoonist for the Washington Post and Washington Star. Includes two autograph albums (1898-1949) containing pen portraits of individuals such as Grover Cleveland, Calvin Coolidge, Dwight D. Eisenhower, Warren G. Harding, Herbert Hoover, William McKinley, Franklin D. Roosevelt, Theodore Roosevelt (next to a sketch of the Teddy Bear), William H. Taft, Harry S. Truman, and Woodrow Wilson. Each portrait is autographed by the subject. Also includes illustrated letters written by Berryman to his mother during his years at the U.S. Patent Office, a lecture with sketches, and an 1814 bill of sale for a woman and child. Correspondents include presidents, vice-presidents, cabinet members, members of Congress, Supreme Court justices, and illustrators, Charles Bittinger and John T. McCutcheon. Many correspondents commented on specific cartoons and thanked Berryman for his gift of original cartoons.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Cartoonist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bittinger, Charles, -- 1879-1970 -- Correspondence; Cleveland, Grover, -- 1837-1908.; Coolidge, Calvin, -- 1872-1933.; Eisenhower, Dwight D. -- 1890-1969.; Harding, Warren G. -- 1865-1923.; Hoover, Herbert, -- 1874-1964.; McCutcheon, John T. -- 1870-1949 -- Correspondence; McKinley, William, -- 1843-1901.; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Theodore, -- 1858-1919.; Taft, William H. -- 1857-1930.; Truman, Harry S., -- 1884-1972.; Wilson, Woodrow, -- 1856-1924.; United States. -- Congress; United States. -- Supreme Court; Washington post; Washington star; American newspapers -- Washington (D.C.); Cabinet officers -- Correspondence; Judges -- United States -- Correspondence; Legislators -- United States -- Correspondence; Political cartoons; Presidents -- United States -- Autographs; Presidents -- United States -- Correspondence; Presidents -- United States -- Portraits; Vice-Presidents -- United States -- Correspondence; Slave bills of sale; Teddy bears; United States -- Politics and government -- Caricatures and cartoons; Cartoonists